2008
DOI: 10.1016/j.micinf.2007.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Serum thyrotropin, thyroxine and free thyroxine concentrations as predictors of mortality in critically ill puppies with parvovirus infection: a model for human paediatric critical illness?

Abstract: This prospective case-controlled study investigated the role of the pituitaryethyroidal axis in the prediction of mortality in dogs. Serum thyrotropin, thyroxine and free thyroxine were measured at admission and daily until death or discharge in dogs ill with parvoviral diarrhoea. Serum thyroxine and free thyroxine in ill dogs were significantly lower than in controls and also significantly lower in nonsurvivors than in survivors on days 1-4. Serum thyrotropin at admission in ill dogs was similar to controls, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
38
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 22 publications
9
38
2
Order By: Relevance
“…Serum D‐lactate concentration was not significantly associated with outcome (survival versus death), leukocyte numbers, or the presence or absence of SIRS. Aside from potential insight into the duration of hospitalization, these findings suggest that serum D‐lactate would not serve as a useful marker when managing CPV infection or prognosticating outcomes, especially when compared to other effective measures in CPV infection such as serum thyroxine or cortisol concentrations or leukocyte changes …”
Section: Discussionmentioning
confidence: 99%
“…Serum D‐lactate concentration was not significantly associated with outcome (survival versus death), leukocyte numbers, or the presence or absence of SIRS. Aside from potential insight into the duration of hospitalization, these findings suggest that serum D‐lactate would not serve as a useful marker when managing CPV infection or prognosticating outcomes, especially when compared to other effective measures in CPV infection such as serum thyroxine or cortisol concentrations or leukocyte changes …”
Section: Discussionmentioning
confidence: 99%
“…Some studies performed in animal models of sepsis or septic shock support the hypothesis that relative thyroid insufficiency is associated with a worse outcome. For example, lower baseline serum T 4 and free T 4 have been associated with decreased likelihood for survival in severely ill dogs (puppies) with parvoviral diarrhea (31).…”
Section: Discussionmentioning
confidence: 99%
“…The only clinicopathological variables associated with poor outcome in cats are leukopenia, lack of increase in leukocyte count after 3 days of hospitalization, thrombocytopenia, hypoalbuminemia, and hypokalemia . In dogs affected by parvoviral infection, serum total thyroxine (tT4) and cholesterol concentrations are significantly lower at hospital admission in nonsurvivors compared with surviving dogs . Furthermore, 2 studies evaluating the prognostic value of acute phase proteins (APPs) in dogs with parvoviral enteritis indicated that C‐reactive protein (CRP) was higher in nonsurviving dogs and positively associated with increased risk of death .…”
Section: Introductionmentioning
confidence: 99%